2016
DOI: 10.1111/mec.13482
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with uncertainty in landscape genetic resistance models: a case of three co‐occurring marsupials

Abstract: Landscape genetics lacks explicit methods for dealing with the uncertainty in landscape resistance estimation, which is particularly problematic when sample sizes of individuals are small. Unless uncertainty can be quantified, valuable but small data sets may be rendered unusable for conservation purposes. We offer a method to quantify uncertainty in landscape resistance estimates using multimodel inference as an improvement over single model-based inference. We illustrate the approach empirically using co-occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 86 publications
3
51
1
Order By: Relevance
“…To validate the resistance maps, we calculated R 2 β statistics and confirmed that they explained an adequate proportion of the sampled genetic variation for each species (mean 0.63 R 2 β ± 0.13 SD ; Supporting Information Table ). We also verified that these statistics are robust to uncertainty using bootstrap analyses (10,000 replicates with 80% of the data; Supporting Information Table ; following Dudaniec et al., ). As mentioned earlier, the analysis originally included one additional species ( G. nivalis ) but it was omitted because its resistance maps had poor predictive abilities ( R 2 β ≤ 0.35; following Keller et al., ).…”
Section: Methodssupporting
confidence: 54%
“…To validate the resistance maps, we calculated R 2 β statistics and confirmed that they explained an adequate proportion of the sampled genetic variation for each species (mean 0.63 R 2 β ± 0.13 SD ; Supporting Information Table ). We also verified that these statistics are robust to uncertainty using bootstrap analyses (10,000 replicates with 80% of the data; Supporting Information Table ; following Dudaniec et al., ). As mentioned earlier, the analysis originally included one additional species ( G. nivalis ) but it was omitted because its resistance maps had poor predictive abilities ( R 2 β ≤ 0.35; following Keller et al., ).…”
Section: Methodssupporting
confidence: 54%
“…We generated multiple resistance surfaces from our parameterized Annual Temp and Land Cover data to test for multiple hypotheses about their effects on genetic distance. To generate alternative resistance surfaces with varying resistance, we applied a similar method as implemented by Dudaniec et al (, ), which is a modified approach of Shirk et al (), whereby different values of intercept ( α ) and slope ( γ ) parameters are used to create linear and nonlinear resistance surfaces. We applied the following formulas to generate resistance relationships:ri=1+α(Ti-1/max-1)γri=1+α(Li-1/max-1)γwhere r i is the resistance of cell i , T i is the Annual Temp of cell i (Equation ), L i is the rank of Land Cover type of cell i (Equation ) and max is the maximum value of the raster surface.…”
Section: Methodsmentioning
confidence: 99%
“…Comparative landscape genetics studies on codistributed species have great potential to design cost‐effective conservation plans focusing on measures favouring a wider set of taxa, but are still relatively scarce. So far, comparative studies have focused primarily on vertebrates, including amphibians (Coster, Babbitt, Cooper, & Kovach, ; Richardson, ; Zancolli, Rödel, Steffan‐Dewenter, & Storfer, ), mammals (Dudaniec et al., ; Frantz et al., ; Muscarella, Murray, Ortt, Russell, & Fleming, ), and fishes (Olsen et al., ) and more occasionally on invertebrates (Engler, Balkenhol, Filz, Habel, & Rödder, ; Ortego, García‐Navas, Noguerales, & Cordero, ; Phillipsen et al., ). These multi‐species studies may allow identifying interspecific differences in the way landscape features influence connectivity and gene flow and provide general guidelines for land management programmes aimed at protecting biological communities or ecosystems (Goldberg & Waits, ; Keller, Holderegger, Strien, & Bolliger, ; Nicholson & Possingham, ; Schwenk & Donovan, ).…”
Section: Introductionmentioning
confidence: 99%